The Creative Process. A Case for Meaning-Making - Setai, Phokeng T.; Coetzee, Jan K.; Maeder, Christoph; Wojciechowska, Magdalena; Ackermann, Leane (Qualitative Sociology Review, 2019)
Since the beginning of time art-making has been a tool to express, preserve, and challenge the extant knowledge in society. Artists do this by finding or creatively constructing new understandings in society. An artist is able to do this through the medium he/she uses to relay the message of the artwork. The medium that an artist uses to express his/her artistic concept has an impact on the character that the artwork will take. The medium of expression forms but one of the many considerations that go through an artist’s mind when creating art. In the process of art-making, an artist seeks to create new meanings or re-imagine old ones by organizing materials and concepts. In so doing, he/she discovers novel ways to get ideas across, and thereby creates new interpretations of social phenomena. In this article, attention is given to meaning-making as a conscious and iterative component of creating art. From a series of in-depth interviews, the authors analyze the inward processes that occur within six artists’ creative praxes and how these lead their construction of meaning. Attention is also paid to how the artists manipulate concepts and how they construct and deconstruct their understandings of these concepts in the course of their creative endeavors.